Treatment of pediatric relapsed and refractory acute myeloid leukemia - F. A. Makhacheva; T. T. Valiev (Онкогематология, 2023)
Background. Despite the modern therapy programs including hematopoietic stem cell transplantation, the treatment outcomes for children with acute myeloid leukemia (AML) remain unsatisfactory. The 5‑year overall survival rate is about 70 %. The 5‑year overall survival rate for patients with relapsed and refractory AML is 2 times lower (about 35 %). The treatment failure rate in primary AML and unsatisfactory results in relapsed and refractory AML make it necessary to optimize therapy protocols.Aim was a long-term retro- and prospective analysis of clinical and laboratory characteristics and treatment outcomes in patients with relapsed and refractory forms of AML.Materials and methods. This article presents the treatment results of 54 patients from 1 to 18 years of age, with relapsed and refractory AML treated at the N. N . Blokhin National Medical Research Center of Oncology from 1997 to 2022.Results. A comparison of 5 different programs revealed that patients who received second remission induction with the FLA + FLA scheme had 81.8 % of response (complete or partial) achievement. Analysis of the results in achievement the second remission in patients received epigenetic agents (azacytidine, decitabine, valproic and all-trans retinoid acids) with second-line chemotherapy found that treatment response rate was 100 % (n = 27), in contrast to patients received only second-line chemotherapy (n = 27) – 81.5 % (p = 0.003). The best treatment results were in group of patients whose treatment included epigenetic agents and allogenic hematopoietic stem cell transplantation after second remission induction – 5‑year overall survival was 51.3 ± 9.7 %.Conclusion. Intensive polychemotherapy with fludarabine- and cytarabine-containing regiments with following allogeneic hematopoietic stem cell transplantation and epigenetic agents are current trend and pathogenetically based approach for relapsed and refractory pediatric AML. Probable, the definition of the role and place of targeted drugs (gemtuzumab ozogamicin) could continue the advances in treatment of such unfavorable patient group.